Beyond the dose‐limiting toxicity period: Dermatologic adverse events of patients on phase 1 trials of the Cancer Therapeutics Evaluation Program. Issue 8 (24th February 2016) - Drilon, Alexander; Eaton, Anne A.; Schindler, Katja; Gounder, Mrinal M.; Spriggs, David R.; Harris, Pamela; Ivy, S. Percy; Iasonos, Alexia; Lacouture, Mario E.; Hyman, David M.
Abstract : BACKGROUND: Dermatologic adverse events (AEs) can be key determinants of overall drug tolerability and of the maximum tolerated and recommended phase 2 doses in phase 1 trials. The authors present the largest dedicated analysis of dermatologic AEs on phase 1 trials to date. METHODS: Data from a prospectively maintained database of patients with solid tumors who were enrolled onto Cancer Therapeutics Evaluation Program (CTEP)‐sponsored phase 1 trials of cytotoxic or molecularly targeted agents (MTAs) from 2000 to 2010 were analyzed. Cumulative incidence, site, and type of drug‐related dermatologic AEs were described and compared. The timing of worst drug‐related dermatologic AEs was summarized. RESULTS: In total, 3517 patients with solid tumors and 6165 unique, drug‐related dermatologic AEs were analyzed, including 1545 patients on MTA‐only trials, 671 on cytotoxic‐only trials, and 1392 on combination MTA and cytotoxic trials. Of 1270 patients who had drug‐related dermatologic events, the timing of the worst AE was as follows: 743 (cycle 1), 303 (cycle 2), and 224 (cycle 3 or later). Although the cumulative incidence of grade ≥3 drug‐related AEs increased to 2.4% by cycle 6, it was only 1.6% at the end of cycle 1. The cumulative incidence of drug‐related AEs was highest in patients who received MTA‐only therapy ( P < .001) and differed by dose level ( P < .001). In patients who received MTA‐only therapy, drug‐related AEs were most common for combination kinase inhibitor‐containing therapy ( P < .001). CONCLUSIONS: A substantial proportion of drug‐related dermatologic AEs occur after the traditional dose‐limiting toxicity monitoring period of phase 1 clinical trials. Future designs should account for late toxicities. Cancer 2016;122:1228–37. © 2016 American Cancer Society . Abstract : In 3517 patients with solid tumors who participate in Cancer Therapeutics Evaluation Program (CTEP)‐sponsored phase 1 trials, a substantial proportion of drug‐related dermatologic adverse events are observed after the traditional dose‐limiting toxicity period. The cumulative incidence of these events is highest in patients who receive molecularly targeted agents, particularly combination kinase inhibitor‐containing therapy.